PERKEBUNAN KELAPA SAWIT DAN KESEJAHTERAAN MASYARAKAT DI KABUPATEN SAMBAS - ME, Wiwin Supriadi (Jurnal Ekonomi Daerah (JEDA), 2013)
ABSTRACTIn accordance with the Law legislation. 24 of 1992, concerning theexpansion of oil palm plantations Kabupaten Sambas Government since 2003 to2011 to develop 52 325 ha with an extensive reach through partnerships with 22private sector companies. Covering an area of 18 973 ha or 36.26% are plantsthat have been produced up to 2012. Velocity and acceleration of the expansion ofoil palm plantations unplanned and uncontrolled in Kabupaten Sambas emergingsocial impacts and the most significant result of the expansion of oil palmplantations is a land dispute between the company and indigenous / local people,farmers and oil palm plantation workers. Quite often it leads to violent conflictand criminalization. Environmental degradation to loss of biodiversity, floods andlandslides every year due to conversion of protected areas to oil palm plantations.Oil palm plantation development has also become a political commodity andinterest of very visible in the construction of the apparatus of the oil palmplantations, has been the arena of political negotiations between politicians withplanters.Keywords: oil palm plantation, palm plantation expansion, the impact of oilpalm plantations